Transitions of deformation mechanisms in new metastable β-titanium Ti-1500G alloy - Yongqiang Ye; Yuanfei Han; Siyuan Zhang; Jianwen Le; Fu Chen; Jiaming Zhang; Chunyu Shen; Guangfa Huang; Shewei Xin; Weijie Lu; Di Zhang (Materials & Design)
Ultrahigh-strength titanium alloy (≥1250 MPa) innovation calls for an integrated framework combining novel deformation processing and microstructural control. However, a confluence of constitutive model and the deformation behavior of a new β-metastable titanium alloys (Ti-4Al-4Mo-4 V-5Cr-2Zr-1Nb, Ti-1500G) remained ambiguous, making the optimization of precise processing parameters is difficult clarified. An integrated response of the flow stress caused by multiple mechanisms initiated softening and work hardening was characterized using a strain-compensated constitutive model, including shear bands, dynamic recovery and dynamic recrystallization (DRX). Particular attention in this work was placed on in-depth understanding the thermal processing sensitivity of deformation mechanisms transformation. A two-dimensional deformation-mechanism map (DMM) as a function of temperature and strain rate was creatively proposed on the basis of energy dissipation efficiency mechanisms. The transition of deformation mechanisms was attributed to the decreasing thermal activation energy from α + β phase region (413.78 kJ/mol) to β phase region (219.24 kJ/mol), accompanied by dynamic phase transformation and activated dynamic α globularization. Otherwise, low strain rates promote α phases-dislocation interactions to accelerate the DRX grains nucleation. The DMM with various physical parameters is an efficient approach for guiding the thermomechanical processing of ultrahigh-strength titanium alloy large-scale components to reduce cracking tendency.